Comparison of the PT/INR assay using two different reagents - Etem, Arzu Akagac; Etem, Ebru; Mizrak, Soycan; Can, Gamze; Salman, Ahmet; Unal, Serpil (Bayrakol Medical Publisher, 2020)
Aim: The Prothrombin time (PT) assay is a coagulation test that shows the activation of the extrinsic and final common pathways. The purpose of the present study was to evaluate the PT/INR levels using BioMedica QuikCoag PT and Technoclone Technoplastin HIS (heparin-insensitive) reagents on Ceveron alpha coagulation instrument. Materials and Methods: The study was conducted in the Usak State Hospital in the west of Turkey. We analyzed 78 patients plasma PT/INR levels utilizing two kits on Ceveron alpha automated coagulation instrument. Results: The mean age of 32 male 46 female patients was 51 +/- 21. The mean value of PT was 14,77 +/- 5,80 with Technoplastin HIS and 20,66 +/- 12,19 with QuikCoag PT. The mean value of INR was 1,42 +/- 0,65 with Technoplastin HIS and 1,67 +/- 1,16 with QuikCoag PT. We obtained a statistically significant difference between PT and INR levels using a two-sample t-test (p=0,000 and p=0,000 respectively). Discussion: Technoplastin HIS PT is a standardized Ca-thromboplastin reagent obtained from the rabbit brain. The values attained utilizing Quik Coag PT kits are not equal to those attained utilizing the Technoplastin HIS PT kits. An independent check of a producer's international sensitivity index (ISI) assignments by a national reference laboratory in Turkey is also proposed.
Keywords: Prothrombin Time; INR; Thromboplastin; Reagent